Synthesis, Characterization and Antifungal Studies of Some Mixed Ligand Schiff Base Complexes of 2-Phenyl-[3-(hydroxy propyl)]-3,1-(4H)-quinazolin-4-one Hydrazone of Co(II), Ni(II) and Cu(II) - RAI, B.K.; RAI, RAJESHWAR; RANA, SWATY; SAHI, POONAM (Asian Journal of Chemistry, 2010)
The preparation and structural studies of some mixed ligand complexes of Co(II), Ni(II) and Cu(II) with 2-phenyl-[3-(hydroxy propyl)]-3,1-(4H)-quinazolin-4-one hydrazone (PHQH) have been carried out by elemental analysis, IR, UV spectra, magnetic susceptibility conductivity measurements and thermal study. The complexes has been found to act as bidentate ligand and the coordination occurs both from azomethine nitrogen and oxygen atoms of hydroxyl group. The remaining coordination sites are occupied by nitrogen atoms of ammonia, pyridine, α-picoline, β-picoline and γ-picoline. The geometry of the complexes are proposed to be octahedral. The ligand PHQH as well as metal complexes have been tested for antifungal study against two species Penicillium expansum and Aspergillus flavus.